THE THE EFFECT OF THERMAL STERILIZATION AND EXCIPIENTS ON THE STABILITY OF ASCORBIC ACID IN AQUEOUS SOLUTIONS - SYROESHKIN, A. V.; PLETENEVA, T. V.; USPENSKAYA, E. V.; LEVITSKAYA, O. V.; BARSEGYAN, S. S.; ZLATSKY, I. A.; TRIBOT-LASPIERE, M. A. (International Journal of Applied Pharmaceutics, 2019)
Objective: To investigate the thermal stability of aqueous solutions of L-ascorbic acid (AA) and its reactions with excipients for the improvement of the injection forms technology. Methods: Solutions of L-ascorbic acid were prepared using deuterium depleted water (DDW-«light» water, D/H=4 ppm) and natural deionized high-ohmic water (BD, D/H=140 ppm). The optical rotation was observed using an automatic polarimeter Atago POL-1/2. Electrospray tandem mass spectra were recorded by Sciex X500R QTOF. Electronic spectra were recorded by UV-spectrometer Cary 60 (Agilent). Unicellular biosensor (Spirotox-test) was used for investigation of excipients influence on the AA biological activity. The statistical analysis was carried out using the OriginPro®9 packages. Results: The results demonstrate the thermal instability of AA. The optical activity of injection forms of AA differs from model solutions with the same concentration and pH value but without heat treatment. Monitoring of solutions by the LC-ESI-MS/MS method made it possible to characterize the nature of some thermal decomposition products. Thermodynamic calculations and evaluation of biological activity (Spirotox-test) indicate that AA interacts with sulfite-ion by redox mechanisms. Excipients in AA aqueous solutions decrease, but DDW increases the biological object lifetime. Conclusion: The use of the set of physicochemical and biological methods to study the effect of heat treatment of L-ascorbic acid solutions in the presence of sulfur (IV) compounds as excipients made it possible to identify decomposition products of the active pharmaceutical ingredient. The results indicate the need to exclude sterilization of the AA injection form by the thermal method and replace it with an alternative one, for example, with gamma radiation treatment.